Storage time effect on ‘Dulce de leche’ characteristics with coffee and whey - Larissa de Oliveira Ferreira Rocha; Sandra Maria Pinto; Luiz Ronaldo de Abreu; Carlos José Pimenta (Acta Scientiarum: Technology, 2017)
The ‘Dulce de leche’ (milk-based caramel sauce) is a product that has good chemical and microbiological stability, but low physical stability. Physical stability refers to the maintenance of fine texture, without the appearance of ‘grittiness’ given by large lactose crystals which are slowly formed during storage, causing great inconvenience in the product preservation. This work was carried out with the objective to verify the storage time effect on physical, physicochemical microbiological and sensory characteristics of the ‘Dulce de leche’ with coffee added whey and modified starch. It was found that the storage time has a significant effect on color variables b* and L* and in parameters texture (hardness, adhesiveness, elasticity, cohesiveness and gumminess). There was no formation of lactose crystals and microbiological quality was maintained throughout ‘Dulce de leche’ storage time. The time did not influence in the ‘Dulce de leche’ acceptance in relation to flavor, texture and overall impression, which shows that variations of color and instrumental texture did not affect the product sensory quality, providing an alternative for the use of whey and coffee in ‘Dulce de leche’ production, thus obtaining a new product.